1983
DOI: 10.1029/ja088ia01p00341
|View full text |Cite
|
Sign up to set email alerts
|

Particle and wave observations of low‐altitude ionospheric ion acceleration events

Abstract: We report energetic ion and electron, wave, and ambient plasma observations from two sounding rockets which were launched from Churchill, Canada, into the expansive phases of two auroral substorms and which passed through source regions of transversely accelerated ionospheric ions (TAI). The two events were observed at low altitudes (400-600 kin) and resulted in ion energization of hundreds of electron volts. In the acceleration region, the ionospheric ion velocity distribution function in the direction perpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…The simplest explanation for their generation is a local, perpendicular energy transfer to cold ions. Such distributions have been mainly observed by sounding rockets, low and mid-altitude satellites (Sharp et al, 1977;Yau et al, 1983;Kintner et al, 1996;André et al, 1988;Whalen et al, 1991). A second type, called elevated or bi-modal conics, has been first identified by Klumpar et al (1984).…”
Section: Introductionmentioning
confidence: 99%
“…The simplest explanation for their generation is a local, perpendicular energy transfer to cold ions. Such distributions have been mainly observed by sounding rockets, low and mid-altitude satellites (Sharp et al, 1977;Yau et al, 1983;Kintner et al, 1996;André et al, 1988;Whalen et al, 1991). A second type, called elevated or bi-modal conics, has been first identified by Klumpar et al (1984).…”
Section: Introductionmentioning
confidence: 99%
“…Ion energization varies from a few eV in the polar wind (BANKS and HOLZER, 1969) to hundreds of eV in transverse ion acceleration (Tai, Conics) events (SHARP et al, 1977;WHALEN et al, 1978;KLUMPAR, 1979;YAU et al, 1983) and may extend into the keV range (SHELLEY et al, 1976) at higher altitudes where magnetic field aligned electric fields are believed to play a significant role in ion energization.…”
Section: Introductionmentioning
confidence: 99%
“…Peterson et al (1993) have presented simultaneous Akebono and DE-1 observations at two different altitudes on (nearly) the same field line in the dayside cusp, which are indicative of the simultaneous occurrence of ion acceleration at two widely separated altitudes on a field line. Yau et al (1983) observed transversely energized ions up to 500 eV on sounding rockets down to 400 km altitude during active aurora. During extended periods of auroral activity, SMS occasionally observes upflowing molecular ions (NO' and N2') in the high-altitude aurora] zone both in the dayside and the nightside .…”
Section: Suprathermal Auroral Ionsmentioning
confidence: 99%